2016
DOI: 10.1007/s00586-016-4615-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, physical, and radiographic analyses of lumbar degenerative kyphosis and spondylolisthesis among community-based cohort

Abstract: Current study showed that DS was associated with reduced trunk flexor strength, which might increase pelvic anteversion, and LDK was associated with reduced extensor strength, ROM, and ambulatory kyphosis. Physical characteristics should be evaluated for the successful management of adult spinal deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…There was no significant change in the values for TK over 34 years, which is similar to the findings of Kobayashi et al who also reported small changes in TK over their study period of 12.3 years [4]. On the other hand, Diebo et al reported a wider range for TK, with spinal malalignment ranging from hyper-to hypokyphosis [27], Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There was no significant change in the values for TK over 34 years, which is similar to the findings of Kobayashi et al who also reported small changes in TK over their study period of 12.3 years [4]. On the other hand, Diebo et al reported a wider range for TK, with spinal malalignment ranging from hyper-to hypokyphosis [27], Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The ultimate aim of ASD treatment, even in younger patients, is to ensure that patients are ambulant without requiring a cane or handrail for support. ASD affects muscular strength leading to changes in the range of motion of the trunk, lower extremities, and the whole body [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Aono et al [83] followed up for 12.1 years (8–14 years) in 142 female subjects without spondylolisthesis at baseline radiographs (mean baseline age: 54.7 years, range: 40–77yrs), and the incidence of newly developed DS was 12.7%. The same group [84] reported when the female participants were 68.5 ± 9.2 years old, the DS prevalence was 24.8% (50 participants out of 289). These data suggest that elderly Japanese females and elderly Chinese females in Hong Kong have similar DS prevalence and progression rates.…”
Section: Epidemiology I: Results Of Population Based Studiessupporting
confidence: 56%
“…To date, ASD studies have focused on the static deformity using upright entire spine radiographs 2,4 , and modalities to evaluate dynamic ambulatory kyphosis are scarce. We reported changes in trunk angle using digitally captured gait postures 5 and found some characteristic changes in arm swing among elderly participants that had not been previously elaborated.…”
Section: Introductionmentioning
confidence: 96%